Pengaruh harga, kualitas produk dan promosi terhadap keputusan pembelian pada produk kacang asin PT. Kacang Asin Pak Tani di Desa Tanjung Anom - Mahesa Dewangga; Eka Umi Kalsumi; Akman Daulay; Yunanda Eka Putra (Fakultas Ekonomi Universitas Al-Azhar Medan, 2026)
This study aims to analyze the influence of Price, Product Quality, and Promotion on Consumer Purchase Decisions of the salted peanut product by PT. Pak Tani in Tanjung Anom Village. The research uses a quantitative approach with a survey method involving 65 respondents who are consumers of the product. Data collection was conducted through questionnaires using a Likert scale, and data were analyzed using multiple linear regression. The results indicate that Product Quality and Promotion variables have a positive and significant influence on Purchase Decisions, while the Price variable does not have a significant effect. The F-test shows that all three independent variables simultaneously have a significant influence on the dependent variable. The Adjusted R Square value of 0.693 indicates that 69.3% of the variability in Purchase Decisions is explained by these three variables.